Do Institutional Ownership and Profitability Increase Firm Value? - Nur Edi Cahyono; Nur Siyami; Wakhdan Wakhdan (International Forum of Researchers and Lecturers, 2025)
This research aims to examine the influence of institutional ownership and profitability variables on company value. The population in this study are Fast Moving Consumer Goods companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique for this research uses the Purposive Sampling Technique where the sample is selected using certain criteria so that in this research 15 companies were obtained over 3 years so that a total of 45 research data were obtained. The data analysis technique used in this research uses statistical analysis which includes multiple correlation, multiple regression, determination tests and hypothesis tests. The results of this research institutional ownership variable obtained a significance value of 0.546>0.05. So it can be concluded that institutional ownership has no effect on company value. Return On Assets variable obtained a significant value of 0.112>0.05. So it can be concluded that Return On Assets has no effect on company value.